2008
DOI: 10.1080/17461390802067679
|View full text |Cite
|
Sign up to set email alerts
|

How students’ perceptions of teachers’ autonomy‐supportive behaviours affect physical activity behaviour: an application of the trans‐contextual model

Abstract: The aim of this study was to assess a modified version of the trans-contextual model (Hagger, Chatzisarantis, Culverhouse, & Biddle, 2003) based on self-determination theory (Deci & Ryan, 1985) and the theory of planned behaviour (Ajzen, 1985). The modified version included two additional components: use of learning strategies and positive general feedback. It was hypothesized that students' perceptions of how they use learning strategies taught by their physical education (PE) teachers and perceived positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 52 publications
3
39
0
8
Order By: Relevance
“…The dimensions consist of autonomous motivation, integrated motivation, and identified motivation which influence consumers" purchase intention. This finding is in line with some previous researches (Hagger et al, 2003;Pihu et al, 2008;Shen et al, 2007) which reported a direct and indirect relationship of self-determination and behavioral intention in terms of health-related behavior. Self-determination can also be employed to measure consumerism, because within the indicators and dimensions of self-determination, the internalization process within the consumers can be seen.…”
Section: A Discussion Of Research Findingssupporting
confidence: 83%
“…The dimensions consist of autonomous motivation, integrated motivation, and identified motivation which influence consumers" purchase intention. This finding is in line with some previous researches (Hagger et al, 2003;Pihu et al, 2008;Shen et al, 2007) which reported a direct and indirect relationship of self-determination and behavioral intention in terms of health-related behavior. Self-determination can also be employed to measure consumerism, because within the indicators and dimensions of self-determination, the internalization process within the consumers can be seen.…”
Section: A Discussion Of Research Findingssupporting
confidence: 83%
“…Using a physical activity lens, research within physical education has investigated the influence of autonomy-supportive environments on PA and PA intentions based predominantly on a theoretical/conceptual framework (Fortier, Duda, Guerin, & Teixeira, 2012;Ryan et al, 2009;Teixeira, Palmeira, & Vansteenkiste, 2012) with a limited number of studies using a more scientific or research based methodology (Hagger et al, 2003(Hagger et al, , 2005Lim & Wang, 2009;Pihu et al, 2008). Each of the theoretical studies supports the notion that engaging students in a highly autonomy-supportive context can facilitate engagement in PA.…”
Section: Social Context and Physical Educationmentioning
confidence: 94%
“…Grounded within self-determination theory (Deci & Ryan, 1985), the social context involves primarily environmental factors, commonly manipulated by the teacher in educational settings, which influence students' desire or motivation (Deci & Ryan, 1985;Vallerand & Losier, 1999). Furthermore, the influence on motivation has ramifications for students' engagement in physically active behaviors (Hagger, Chatzisarantis, Barkoukis, Wang, & Baranowski, 2005;Pihu, Hein, Koka, & Hagger, 2008;Vallerand & Losier, 1999). Aspects of the social context have been identified as facilitating a variety of positive student outcomes and experiences, including higher attendance rates (Edmunds, Ntoumanis, & Duda, 2006), motivation (Perlman, 2011a(Perlman, , 2011bPerlman & Goc Karp, 2010), leisure time PA (Hagger, Chatzisarantis, Culverhouse, & Biddle, 2003) and intention toward engaging in physical activity (Lim & Wang, 2009).…”
Section: Social Contextmentioning
confidence: 99%
“…One of the major limitations is the omission of measures about students' autonomous motivation towards leisuretime physical activity, as well as situation-specifi c beliefs and judgements about leisure-time physical activity behaviour, specifi ed in the theory of planned behaviour [1]. Past studies have demonstrated that autonomous motivation towards PE has an impact to actual leisure-time physical activity behaviour indirectly through the autonomous motivation towards leisure-time physical activity and constructs from the theory of planned behaviour about leisuretime physical activity behaviour [2,11,12,21]. Second limitation pertains to the correlational nature of the data that precludes the inference of causality.…”
Section: Discussionmentioning
confidence: 99%